Pengaruh Kualitas Pelayanan Pajak dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan - Purnamasari, Dyah; Sari , Diana; Mulyati, Yati (Politeknik Ganesha Medan, 2024)
This study aims to determine the effect of service quality and taxpayer awareness on land and building taxpayer compliance at the UPT Regional Revenue Agency for the South Bandung region. The factors examined in this study are Service Quality and Taxpayer Awareness as independent variables and Land and Building Taxpayer Compliance as the dependent variable. The method used in this research is a quantitative research method with a survey approach. The population in this study are land and building taxpayers who are registered at the UPT BAPENDA South Bandung Region, totaling 442,987 taxpayers.. The data analysis technique used is multiple linear regression analysis. Based on the results of the study it can be concluded that the influence of Service Quality and Taxpayer Awareness has an effect on Land and Building Taxpayer Compliance at UPT BAPENDA South Bandung Region. The better the quality of tax services and the better the awareness of the Taxpayer, the more Taxpayer compliance will increase.